(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Objective: To observe the correlation between fine needle aspiration cytology (FNAC) and Histopathology in the diagnosis of thyroid lesions. Methods:It was a Retrospective record review study .One hundred four (104) Patients with enlarged thyroid gland of both sexes were selected from admitted patients of National institute of ENT, Tejgaon, Dhaka, Duration was from January 2017 to December 2018. Every patients had preoperative FNAC & postoperative histopathology report of thyroid lesions. Results: FNACdiagnosis of thyroid lesions were correlated with histopathology diagnosis. Out of 104 patients 26 were male 78 were female. Male-Female ratio were 1:3.out of 104 patients most Patients were 31 to 40 years of ageGroup.out of 104 cases of FNAC 9 cases were false Cyto-diagnosis. Overall accuracy rate was 91.35%. Conclusion: FNAC is a reliable, safe and relatively accurate method as apreoperative evaluationin thyroid gland swelling before surgery. FNAC has more accuracy in detecting thyroid gland malignancy and therefore it is a reliable diagnostic test for evaluation of thyroid swelling. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 81-85